Development of agriculture safety and health risk assessment matrix (ASHRAM) with an integrated modifying risk factor elements - Baharudin, Mohd Rafee; Jamaludin, Murni Illani; Mohd Elias, Saliza; Dahlan, Nur Dalilah (Malaysian Public Health Physicians’ Association, 2024)
Risk assessment matrix (RAM) is a tool that is universally utilized across all sectors to mitigate risk. Hazard and risk prevails in every sectors differs between sectors due to the dynamic environment and work activities. Agriculture, considered as one of the hazardous sectors has its own hazard and risk exposed. A suitable RAM therefore should be used to achieve the targeted objective in mitigating risk. An element of risk control measure need to be integrated for an effective control measures. Thus, this paper aims to explain the process of developing Agriculture Safety and Health Risk Assessment Matrix (ASHRAM) specifically developed for agriculture sector with integrating modifying risk factor elements. The framework of ASHRAM development was based on historical accident data and data collected from questionnaire.